Export-led growth hypothesis in Southeast Asia countries: the case of Malaysia / Nur Aqilah Rosli - Rosli, Nur Aqilah (Faculty of Business Management, 2017)
Export has become one of the biggest inflow for economic growth, so success of export-led growth is the best interest for trade policy purposes. That is why most of the countries will try to export their goods or services throughout the world in order to generate higher country inflows than outflows. Therefore, many researchers have done research on export-led growth in many countries to look at the country economic growth like gross domestic product. This research conducts a study for Malaysia which is one of the Southeast Asia countries that export product outside a country. Other than that, the aims of this research is to identifies the relationship between the gross domestic product with the macroeconomic variables. The variables include export, import, gross capital formation and exchange rate. To test this research, the study uses multiple linear regression analysis while the data is taken annually from the year 1961 until 2015.